EVALUATION OF TERRITORIAL COMPETITIVENESS. CASE STUDY: SOUTH – EAST REGION AND TULCEA COUNTY - Mihai Alexandru CHIȚEA; Ion DONA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The concept of competitiveness still represents an important debate subject for the academic and economic environment. Differences of opinion regarding its nature, of macro or micro economic, continue to motivate the identification of common elements that can constitute a widely accepted framework. The common point of these approaches seams to be represented by productivity, regardless of the aggregation level. The different ways of expressing productivity, thou, lead to different models for evaluating competitiveness, of which, the best known are applied at national and regional level. For the evaluation of local competitiveness, specific models have been elaborated, at international and European level, based on representative indices for the investigating areas. The present paper aims to evaluate the competitiveness at county level, compared to the upper aggregation level, namely the Tulcea County and South-East development region, based on a model adapted to the local specifics, represented by the available data sources and structure of relevant indices for this level. The initial hypothesis is that the competitiveness at county level is strongly influenced by the dominant economic character and available resources, both of human and knowledge nature.